Enhanced Mobility Aid for the Visually Impaired - Shahzor Memon; Mirza Muhammad Aamir; Sadiq Ur Rehman; Halar Mustafa; Muhammad Shakir Sheikh (Memoria Investigaciones en Ingeniería, 2025)
This study introduces a smart walking stick for the blind and visually impaired that uses ultrasonic sensors with Arduino and Raspberry Pi. The World Health Organization estimates that 37 million people worldwide are blind. People who are blind or visually impaired frequently rely on assistance from outside sources, which may come in the form of humans, dogs that have been trained, or specialized technological gadgets that play the role of decision-making support systems. We were then inspired to create a smart walking stick in order to get around these restrictions. In order to achieve this, we fitted the stick with ultrasonic sensors at strategic locations that activated the buzzer sound while giving the user information about the surroundings. Our proposal was for a low-cost, lightweight device that uses a microcontroller to interpret signals and emit beeps to notify the visually impaired individual of any obstacles, water, or dark places. The system consists of obstacle and moisture detection sensors that receive, process, and send signals to the alarm system, which then warns the user to take action. The system was conceived and programmed in C, tested for accuracy, and checked by a visually challenged individual. Our technology can identify obstructions within around 2 meters of the user.